High Gain and Radiation Efficiency Rectangular on-Chip Microstrip Patch Antenna for 60 GHz Applications - Malhat, H. A.; Abdelhamied, S.; Zainud-Deen, S. H. (Journal of Advanced Research in Applied Mechanics, 2020)
This paper introduces the design of the X-shaped unit-cell artificial magnetic conductor for rectangular on-chip microstrip patch antenna. The antenna with 50 ? CPW for 60 GHz applications is proposed. The radiation characteristics of the antenna are analyzed and simulated using the finite integration technique, FIT. An X-shaped AMC plane is utilized as an electromagnetic shield beneath the on-chip patch antenna for gain and radiation efficiency enhancement. Different configurations of the AMC planes are employed, full plane, 10×10 AMC units removed blank plane, 6×7 AMC units removed blank plane, and 4×5 AMC units removed blank plane. The full AMC plane introduces gain enhancement of 1.15 dBi and radiation efficiency improvement of 10 % compared to that without AMC case. A depletion layer is employed for more enhancements in the performance of the on-chip patch antenna. This procedure boosts the gain and the radiation efficiency to 4.2 dBi and 79 % respectively.